PERLINDUNGAN ANAK DITINJAU DARI HUKUM ISLAM DAN HAK ASASI MANUSIA (ANALISIS TERHADAP UNDANG-UNDANG NOMOR 17 TAHUN 2016) - Satiman; Abdur Rahim (Melati Institute, 2022)
This research is motivated by the rise of cases of sexual violence against children in recent years. Indonesia is currently in an emergency status of sexual violence against children. Many people say that Indonesia is in a state of emergency for sexual violence. The National Commission for Child Protection (Komnas PA), stated that cases of sexual violence against children over the last five years have shown an increase, there have been 21,689,987 complaints of violations of children's rights spread across 33 Provinces and 202 districts/cities. Of that figure, 42.58% of them were sexual violence. The number of complaints of violations of children's rights which continues to increase is one of the parameters indicating that Indonesia is in an emergency condition of sexual violence against children. The purpose of this study is to find out the views of Islamic law and human rights (HAM) related to law number 17 of 2016 concerning child protection. This type of research is a literature study. The author uses the Normative Law research approach, which is an approach that uses and pays attention to the norms, rules and regulations that apply. The data that has been obtained is analyzed qualitatively and then presented for the purpose of drawing conclusions. The results of the research include: First, Islamic law never prescribes castration. The punishment for castration is unlawful according to Islamic law. secondly, castration is not included in the Criminal Code, so it does not have a strong legal basis in laws and is not in line with Indonesia's criminal convictions. Chemical castration punishment has also elicited a strong international reaction because it is considered a violation of Human Rights (HAM) as a form of torture, and other cruel, inhuman or degrading treatment or punishment as well as a violation of the right to life, even though Indonesia has ratified the Convention on Human Rights. Man.